2005
DOI: 10.1002/ajmg.c.30049
|View full text |Cite
|
Sign up to set email alerts
|

Embryology of neural tube development

Abstract: Neurulation is the process of forming the neural tube, which will become the brain and spinal cord. This article reviews the various cellular processes involved in neurulation and discusses possible roles of folate in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(130 citation statements)
references
References 52 publications
3
111
0
15
Order By: Relevance
“…These cells, termed the "caudal cell mass," coalesce and then epithelialize to form a separate neural tube that will connect with the neural tube formed by the primary neurulation. 21,22 The exact level where the 2 neural tubes meet is still debatable, ranging from the upper conus 23 to the lowest sacral level of the conus 21 ; however, it is agreed that the caudal cell mass will give rise to the filum terminale and the cauda equina. Thus, the embryologic origin of FTAVFs and rAVSs below the conus is associated with secondary neurulation, differing from the remainder of intradural spinal vascular shunt origins that are associated with the primary neurulation.…”
Section: Embryologic Considerationmentioning
confidence: 99%
“…These cells, termed the "caudal cell mass," coalesce and then epithelialize to form a separate neural tube that will connect with the neural tube formed by the primary neurulation. 21,22 The exact level where the 2 neural tubes meet is still debatable, ranging from the upper conus 23 to the lowest sacral level of the conus 21 ; however, it is agreed that the caudal cell mass will give rise to the filum terminale and the cauda equina. Thus, the embryologic origin of FTAVFs and rAVSs below the conus is associated with secondary neurulation, differing from the remainder of intradural spinal vascular shunt origins that are associated with the primary neurulation.…”
Section: Embryologic Considerationmentioning
confidence: 99%
“…Within the central nervous system, pluripotent stem cells turn into NSCs and then to neurons and glial cells. This complex pathway is guided by a series of very specific proteins, which bind to regions of DNA and as a result influence the function of other proteins [4]. All of these interactions result in changes to the identity of the cells.…”
Section: How Do Scientists Make Ipscs Nscs and Neurons Today?mentioning
confidence: 99%
“…NTDs are the most common and severe congenital malformations of the central nervous system, occurring secondary to lack of closure of the neural tube and leading to long-term morbidity. Neurulation, the process of neural tube formation, is completed 28 days after conception, as many women do not realize that they are pregnant at this stage [26]. Das et al found in the systematic review that folate fortification had a significant impact on reducing neural tube defects (risk ratio; RR: 0.57 (95% CI: 0.45, 0.73)), spina bifida (RR: 0.64 (95% CI: 0.57, 0.71)), and anencephaly (RR: 0.80 (95% CI: 0.73, 0.87)).…”
Section: Folate Metabolism and Reproductive Functionmentioning
confidence: 99%